2019
DOI: 10.5382/econgeo.2019.4622
|View full text |Cite
|
Sign up to set email alerts
|

Diatremes Act as Fluid Conduits for Zn-Pb Mineralization in the SW Irish Ore Field

Abstract: Irish-type mineralization is commonly attributed to fault-controlled mixing of a seawater-derived, sulfur-rich fluid and basement-derived, metal-rich fluid. However, maar-diatreme volcanoes discovered in close spatial and temporal association with Zn-Pb mineralization at Stonepark in the Limerick basin (southwest Ireland) bring a new dimension to established geologic models and may increase the deposit-scale prospectivity in one of the world's greatest Zn-Pb districts. Stonepark exhibits many incidences of dol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The Waulsortian Limestone is considered to have been deposited at greater water depths (~200 m) than the Ballysteen Formation [15], between the photic and aphotic zones [16]. Associated with this extensional period of the Lower Carboniferous, mafic intrusions and volcaniclastic rocks are common, mainly in the southwest Irish Midlands in the Limerick area [5,[18][19][20].…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Waulsortian Limestone is considered to have been deposited at greater water depths (~200 m) than the Ballysteen Formation [15], between the photic and aphotic zones [16]. Associated with this extensional period of the Lower Carboniferous, mafic intrusions and volcaniclastic rocks are common, mainly in the southwest Irish Midlands in the Limerick area [5,[18][19][20].…”
Section: Geological Settingmentioning
confidence: 99%
“…However, a recent Re-Os dating has shown that vein-hosted Cu deposits can be slightly older than the Irish Zn-Pb deposits [45]. Furthermore, the spatial and temporal relationship between the mineralization and volcanic rocks from southern Irish Midlands suggests a genetic relation between magmatism and Zn-Pb/Cu-Ag mineralization [5,20]. The magmatic activity has been considered a possible source of heat and water for the Zn-Pb and Cu-Ag mineralizing fluids [5,6,19,20,46].…”
Section: Carbonate-hosted Zn-pb and Cu-ag Mineralization In Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…T, pH and fO 2 ) of a single hydrothermal fluid could cause sulphide precipitation, mostly sulphide mineralization is related to mixing of at least two fluids with contrasting components (e.g. sulphur-rich, metal-depleted brine and metal-rich, sulphur-poor hydrothermal fluid) (Ashton et al, 1998;Blakeman et al 2002;Wilkinson et al 2005;Bouabdellah et al 2008Bouabdellah et al , 2012Barrie et al 2009;Gagnevin et al 2014;Saintilan et al 2015;Elliott et al 2019). Compared to conventional bulk sulphur isotopic analysis, microscale variations in sulphur isotopes obtained by in situ analysis of sulphide minerals reveal more details of mineralizing processes (Deloule et al 1986;Layne et al 1991;McKibben & Eldridge, 1995;Peevler et al 2003;Ferrini et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…pyrite, sphalerite and chalcopyrite) can constrain the mechanisms of metal precipitation, particularly regarding Pb–Zn mineralization hosted by carbonate rocks. It has been suggested that the main sulphur sources for carbonate-hosted Pb–Zn deposits generally include evaporite-derived sulphur (heavy δ 34 S values), previously deposited bacteriogenic sulphur (light δ 34 S values) and magma-derived sulphur (intermediate δ 34 S values) (Perona et al ., 2018; Elliott et al 2019). Although a change in physicochemical conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%